Room-temperature band-edge photoluminescence of GaAs irradiated with medium-energy N+ ions - V.M. Mikoushkin; D.A. Novikov; E.A. Markova; A.E. Kalyadin; N.A. Sobolev; E.A. Grebenshchikova; K.V. Karabeshkin (Results in Surfaces and Interfaces)
The implanted semiconductors need annealing-induced restoration of luminescent and electrical properties for further applications. However, it is still unknown how the effect of the extra-defect formation near the surface influences on the reduction process, as is the magnitude of this effect in GaAs. To confirm the effect and study its influence on luminescence properties of the implanted GaAs based semiconductors, the room-temperature band-edge photoluminescence (PL) spectra were measured before and after the removal of a near-surface layer ∼100 nm thick for GaAs implanted with N+ ions at energies of 30–250 keV with fluence ∼ 1 × 1016 cm−2, followed by annealing at 700oC for several minutes. An increase in the intensity of the PL line by a factor of 1.3–1.6 was found in different samples, indicating the presence of a high concentration of radiation defects in the near-surface layer after annealing. It was shown that the density of the surface defects is several times higher than the maximum density of point defects in the bulk, calculated using the TRIM program and measured previously. Annealing was shown not to restore the surface part of the implanted GaAs layer and its PL. This fact was explained by the clustering of point defects and the oxygen atoms recoiled from native oxide followed by forming chemical bonds with native atoms, which leads to the creation of stable defects irremovable by annealing. The conclusion was made that to increase the PL of implanted GaAs, it is necessary to remove the surface layer.